2015
DOI: 10.1007/s00267-015-0597-7
|View full text |Cite
|
Sign up to set email alerts
|

Does Place Attachment Predict Wildfire Mitigation and Preparedness? A Comparison of Wildland–Urban Interface and Rural Communities

Abstract: Wildfires are a common occurrence in many countries and are predicted to increase as we experience the effects of climate change. As more people are expected to be affected by fires, it is important to increase people's wildfire mitigation and preparation. Place attachment has been theorized to be related to mitigation and preparation. The present study examined place attachment and wildfire mitigation and preparation in two Australian samples, one rural and one on the wildland-urban interface. The study consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 32 publications
6
40
0
Order By: Relevance
“…Age is an important influence on whether residents perform either heavy or full fuel reduction mitigations on their properties. That finding is consistent with existing research because heavy or full fuel reduction would be more difficult for older residents to accomplish (e.g., felling trees, cutting down brush in a larger area) (Anton and Lawrence 2016;Meldrum et al 2014). …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Age is an important influence on whether residents perform either heavy or full fuel reduction mitigations on their properties. That finding is consistent with existing research because heavy or full fuel reduction would be more difficult for older residents to accomplish (e.g., felling trees, cutting down brush in a larger area) (Anton and Lawrence 2016;Meldrum et al 2014). …”
Section: Discussionsupporting
confidence: 85%
“…Research on the factors that predict or influence performance of residential wildfire mitigation strategies are a predominant focus of wildfire social science. Mitigation strategies commonly studied include a host of activities designed to Environmental Management reduce or modify flammable vegetation near structures, use of fire-resistant building materials, clearing gutters of pine needles, and moving firewood away from the home (Anton and Lawrence 2016). This research focuses then on what we could call indicators of adaptive capacity.…”
Section: Vulnerability To Wildfirementioning
confidence: 99%
See 1 more Smart Citation
“…Place attachment refers to the degree of connection that people have with a natural or human-made place [58], and is suggested to be an important predictor of disaster preparedness [8,59]. Studies have shown that if people have an emotional connection to a place, they are more likely to be inspired to plan and reorganize themselves for a disaster in order to continue staying there [60,61].…”
Section: Perceived Flexibility In the Face Of Changementioning
confidence: 99%
“…Disaster preparedness is a multidimensional construct comprising individual physical and psychological preparedness as well as community preparedness [8]. At an individual level, people need to be both physically and psychologically prepared for natural disasters [9].…”
Section: Introductionmentioning
confidence: 99%